ANALISIS KARAKTER TOKOH UTAMA DALAM NOVEL CINTA YANG TAK BIASA KARYA NATTA REZA DAN WARDAH MAULINA (Tinjauan Psikologi Sastra) - Erlina, Erlina (Ensiklopedia of Journal, 2025)
The writing of this article was motivated by character analysis of the main character in Cinta Yang Tak Biasa novel by Natta Reza and Wardah Maulina. Character is the psychological traits, morals and manners that differentiate a person from others. The disclosure of a character's character can be seen through conversations or actions, and direct statements from the character. The type of research used is a descriptive qualitative research method with a phenomenological approach. The object of this research is Cinta Yang Tak Biasa novel by Natta Reza and Wardah Maulina. The data source in this research is the Cinta Yang Tak Biasa novel by Natta Reza and Wardah Maulina, which consists of 230 pages, published in 2017. The results of this research show that the determination of the main character in living his life story has taken him from the lowest point to finally being successful in terms of business and work, as well as in their home life.Keywords: novel, love, characters and characterization, life journey.